2014
DOI: 10.1007/s13277-014-2531-7
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic LC3B overexpression correlates with malignant progression and predicts a poor prognosis in hepatocellular carcinoma

Abstract: Autophagy is a process that involves lysosomal degradations of cellular organelles and closely related to tumor occurrence and progression. However, its importance in hepatocellular carcinoma (HCC) was still controversial. Therefore, this study is aimed to address the clinicopathologic effect of microtubule-associated protein 1 light chain 3B (LC3B) and Beclin-1, as autophagic markers, in HCC patients. Tissue microarray-based immunohistochemistry was used to examine the expression of LC3B and another autophagy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 37 publications
4
57
2
1
Order By: Relevance
“…37,38 In contrast to our melanoma data, Wu and colleagues described MAP1LC3B overexpression in hepatocellular carcinoma and its correlation with malignant progression and poor prognosis. 39 Interestingly, our study showed down-regulation of MAP1LC3B in melanoma cells, which was previously and concordantly with our findings observed in hypopharyngeal squamous cell carcinoma (HSCC) correlating with poor prognosis. 40 Therefore, we speculate that the status and role of MAP1LC3 expression vary across cancer types.…”
Section: Genesupporting
confidence: 92%
“…37,38 In contrast to our melanoma data, Wu and colleagues described MAP1LC3B overexpression in hepatocellular carcinoma and its correlation with malignant progression and poor prognosis. 39 Interestingly, our study showed down-regulation of MAP1LC3B in melanoma cells, which was previously and concordantly with our findings observed in hypopharyngeal squamous cell carcinoma (HSCC) correlating with poor prognosis. 40 Therefore, we speculate that the status and role of MAP1LC3 expression vary across cancer types.…”
Section: Genesupporting
confidence: 92%
“…LC3, the mammalian homolog of the yeast Atg8p, is considered as the crucial component of autophagosomes (Maruyama et al 2014). It includes three isoforms of LC3A, LC3B, LC3C, of which LC3B is associated with autophagy levels (Wu et al 2014a). LC3 has been reported in several tumors (including ovarian cancer (Shen et al 2008), brain cancer (Ghavami et al 2014), colorectal cancer (Wu et al 2015), prostate cancer (Zhang et al 2017), breast cancer (Jiang et al 2017), melanoma (Segala et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of LC3 expression in terms of clinical outcomes have reported controversial results. [21][22][23] Our previous work showed that high LC3 levels in both the liver and tumor microenvironments are significantly correlated with decreased HCC recurrence and increased OS after surgical resection. High LC3 expression seems to have a protective effect on clinical outcomes, including HCC recurrence and OS after hepatectomy.…”
Section: Discussionmentioning
confidence: 99%